Victimization of teachers by students in Israel and in Chile and its relations with teachers’ victimization of students - Benbenishty, Rami; Astor, Ron A.; López, Verónica; Bilbao, Marian; Ascorra, Paula (Aggressive behavior, 2019)
Although in recent years there has been a growing interest in victimization of teachers by their students (student‐to‐teacher victimization), it is not discussed in relation to students’ victimization by their teachers (teacher‐to‐student victimization) across cultures. This study used a cross‐cultural comparative design to examine the prevalence of students’ reports of student‐to‐teacher and teacher‐to‐student victimization and the correlations between them, both at the student and the school levels. It compares the patterns of findings among Jewish and Arab students in Israel and a sample of Chilean students. A nationally representative student sample in Israel (N = 24,243 students from 474 schools) and a Chilean purposeful sample (N = 24,243 students from 37 schools) answered questions regarding being victimized by teachers, and victimizing their teachers. Four cultural groups were compared: Jewish secular, Jewish religious, Arab, and Chilean students. Findings indicate that students reported that they victimized their teachers more verbally than physically. They also reported being victimized by their teachers, more verbally and less physically and sexually. These patterns were quite similar across the cultural groups, although there were significant differences between them in the prevalence of student‐to‐teacher and teacher‐to‐student victimization. The two types of victimization were associated: students who reported being victimized by teachers also tended to report that they victimized teachers, and schools in which teacher‐to‐student victimization was more prevalent were also schools in which student‐to‐teacher victimization tended to be more frequent. We discuss these findings both theoretically and regarding their implications for policy and practice.